Reductions in sprint paddling ability and countermovement jump performance after surfing training - Secomb, J. L.; Sheppard, J. M.; Dascombe, B. J. (The Journal of Strength and Conditioning Research, 2015)
The present study aimed to determine whether any meaningful change in a surfer's sprint paddling ability and countermovement jump (CMJ) performance developed after a 2-hour surfing training session and also whether any physical demands of the surfing session were related to the resultant changes in the capacities. Fifteen competitive male surfing athletes (age, 22.1 ± 3.9 years; height, 175.4 ± 6.4 cm; body mass, 72.5 ± 7.7 kg) performed a 2-hour surfing training session, with 15-m sprint paddle and CMJ trials performed both before and after the surfing session. Pre- to posttesting measures were analyzed using magnitude-based inferences. Likely declines were observed in the velocity achieved at the 5-, 10-, and 15-m splits of the 15-m sprint paddle, as well as peak velocity. Similarly, likely declines were calculated for CMJ peak force, relative peak force, and jump height. Furthermore, large correlations were calculated between presurfing session peak velocity and the change in 5, 10, 15 m, and peak velocity of the 15-m sprint paddle and total distance covered, wave riding bouts, and success rate. Surfing athletes and coaches may need to consider implementing shorter duration training sessions to reduce the decline in sprint paddling ability and CMJ performance. Furthermore, surfing athletes should possess highly developed sprint paddling ability because this may allow them to undertake a greater workload and catch more waves, which will increase the opportunity for technical refinement of maneuvers and skill acquisition.